Separate Worlds? Explaining the current wave of regional economic polarization. (14th March 2018) - Storper, Michael
Abstract: Interregional and intermetropolitan economic divergence is greater in many western developed countries than it has been in many decades. Divergence manifests itself in many ways, including per capita income, labor force participation, and the spatial distribution of skills and returns to education. At the same time, geographical polarization of political preferences and electoral choices has increased, with gains in populism and nationalism in some regions, and broadening of socially liberal, pro-trade and multicultural attitudes in other regions. The task of explaining these developments poses challenges to economic geography and regional and urban economics. These fields have already developed some of the building blocks of an account, but a number of important gaps persist. This article is devoted to identifying priorities for regional science and urban economics, the new economic geography and proper economic geography to tackle the key mechanisms behind divergence as well as to integrate them in a common overall framework.